Escuela Náutica de Manila Scientific Education in the Spanish Philippines - Ay-ad, Philip Vergel (Philippine Studies: Historical and Ethnographic Viewpoints, 2021)
Science education in the nineteenth-century Philippines has been portrayed as highly deficient, yet pockets of respectable scientific education existed. The Escuela Náutica de Manila, which opened in 1820, offered such an education. Thisarticle narrates its establishment and discusses its changing curricular offerings in relation to empire-wide initiatives and constraints internal to the Philippines. Its quality of scientific education can be glimpsed from reports related to three episodes: the earthquake in 1863; the planned closure of the school in the late 1880s; and the advent of American colonial rule in the early 1900s. This school survives as the Philippine Merchant Marine Academy.